Echinococcosis - Inceboz, Tonay (IntechOpen, 2017)
Echinococcosis is an important zoonotic helminth disease all over the world, since some forms may be fatal. The most common species leading to echinococcosis are Echinococcus granulosus, Echinococcus multilocularis, Echinococcus vogeli, and Echinococcus oligarthrus. Although it has been known for many years, it keeps its interesting features. In this book, we aimed to update our knowledge on echinococcosis, focusing on current research advances, new horizons for drug therapy, and surgical management including surgical complications. I cordially believe that this book on echinococcosis will also motivate the future scientists to accomplish more studies on this issue.